KONTRIBUSI PERCEPATAN INKLUSI DAN LITERASI KEUANGAN BAGI KINERJA UMKM KULINER DI KOTA SURAKARTA - Gustita Putri; Helga Arqila Santoso; Purwanto Purwanto (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
Economic development The Micro, Small and Medium Enterprises (MSMEs) sector has a high influence on the Gross Domestic Product (GDP), which is 7% of the total GDP in 2012 (Kementerian Koperasi dan UMKM RI, 2013). The contribution of MSMEs has shown tangible results in the national economy, but MSMEs still find several obstacles such as limited working capital, limited technology, production, marketing and restrictions on business quality and human resources (Anggraeni, 2019). This will have an impact on performance if business actors are not able to manage properly. Business performance usually has a special measure and can measure the success of a business in obtaining profits (Kusumadewi, 2020). The main factor that often makes the financial performance of MSMEs grow is access to capital. Another influential factor is the expansion of financial access followed by knowledge in the financial sector also has an impact on increasing economic growth (Yanti, 2019). This study aims to test whether financial inclusion and financial literacy influence the performance of MSMEs in the culinary sector in Surakarta City. The sample in this study amounted to 100 respondents. The data is then processed using smart PLS. The results of the research hypothesis test shows that financial inclusion and literacy have a significant and positive influence on the performance of MSMEs in the culinary sector in Surakarta City.